The Effects Of Rights Issue Announcement On Stock Price Behaviour In Bursa Malaysia - Kan, Lye Leng (2007)
This study first examines the effects of rights issue announcements by Malaysian listed companies from the period of 1st April 1999 to 31st March 2007 on the stock price behaviour. In an event study using risk-adjusted returns model to calculate abnormal returns, a statistically significant positive average abnormal return immediately after the announcement day is documented.